Service Quality and Behavioral Intentions: A Study of Hong Kong Mobile Services Industry - Leung, Man Huen Jenny (2006)
Studies on service quality are popular but specifically on service quality of mobile network services industry in Hong Kong are scarce. This paper aims at developing a service quality dimension for the mobile network services industry in Hong Kong. The study investigates the service quality of the six network operators in Hong Kong and explores the determinants of service quality in the industry. It studies the impact of service quality on both customer satisfaction and behavioral intentions. In this study, six service quality dimensions, which are Empathy, Responsiveness, Network Quality, Reliability, Assurance, and Tangibles, are developed specifically for the industry. Network Quality is salient in determining both overall service quality and customer satisfaction. Finally, the results are discussed.